2022
DOI: 10.3389/fneur.2022.952900
|View full text |Cite
|
Sign up to set email alerts
|

Perampanel and childhood absence epilepsy: A real life experience

Abstract: ObjectivesThe aim of our study was to evaluate the effectiveness and tolerability of perampanel (PER) as first add-on and as second line monotherapy in subjects with childhood absence epilepsy.MethodsOur sample consisted of 20 patients with childhood absence epilepsy, aged between 8 and 10, already in therapy with a first antiseizure medication with incomplete seizure control. PER was added as first add-on in a dose ranging from 3 to 8 mg/die with 1- 2 mg/week increments. The patients that were seizure-free we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Results regarding absence seizure are supported by another study that evaluated PER as the first add-on and second-line monotherapy in 20 subjects with CAE (16). Overall, 75% of patients were seizurefree with add-on therapy, and 60% remained seizure-free with PER monotherapy.…”
Section: Idiopathic and Genetic Generalized Epilepsymentioning
confidence: 64%
See 2 more Smart Citations
“…Results regarding absence seizure are supported by another study that evaluated PER as the first add-on and second-line monotherapy in 20 subjects with CAE (16). Overall, 75% of patients were seizurefree with add-on therapy, and 60% remained seizure-free with PER monotherapy.…”
Section: Idiopathic and Genetic Generalized Epilepsymentioning
confidence: 64%
“…Mild, transient side effects were reported only by two and did not lead to PER discontinuation. Moreover, PER did not negatively affect non-verbal intelligence, executive functions, emotional and behavioral symptoms, and parental stress (16).…”
Section: Idiopathic and Genetic Generalized Epilepsymentioning
confidence: 75%
See 1 more Smart Citation
“…In the IGE group, the responder and seizure freedom rates were substantially lower than those observed in the current study; however, this is likely to reflect that PWE in the study were more refractory to treatment than those included in PERMIT, because 56.7% were being treated with ≥3 concomitant ASMs at baseline 25 (compared with 25.3% in the current study). The fifth study was an Italian, single‐center, retrospective, observational study, which demonstrated that PER was effective and well tolerated as first add‐on and second‐line monotherapy in 20 PWE with childhood absence epilepsy over a mean follow‐up duration of 10.2 months 26 . The final study was an Italian, multicenter, observational, retrospective study, in which PER was shown to be effective and well tolerated as only add‐on therapy in 503 PWE with focal, generalized, or undetermined epilepsy treated for up to 12 months, although outcomes were not reported separately for PWE with generalized epilepsy 27 …”
Section: Discussionmentioning
confidence: 99%
“…Approval of PER for the treatment of GTCS in IGE was based on the results of one phase 3, randomized, double‐blind, placebo‐controlled trial 17,18 . Clinical practice studies provide evidence on how a drug performs when used outside the relative restrictions of clinical trials, 19–21 but real‐world evidence on the use of PER to specifically treat IGE is currently limited 22–27 …”
Section: Introductionmentioning
confidence: 99%